2012
DOI: 10.4049/jimmunol.1200486
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Immunoreactivity between Bacterial Aquaporin-Z and Human Aquaporin-4: Potential Relevance to Neuromyelitis Optica

Abstract: Neuromyelitis optica (NMO) is a chronic inflammatory disease of the CNS that is mediated, in part, by a self-reactive Ab against the astrocyte aquaporin-4 protein. In the current study, we examined the possibility and the biological significance of cross-immunoreactivity between bacterial aquaporin-Z and human aquaporin-4 proteins. Sequence-alignment analysis of these proteins revealed several regions of significant structural homology. Some of the homologous regions were also found to overlap with important i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…Aquaporin Z was found in all GS2 C. concisus strains, but not in any GS1 strains. Aquaporin Z is a protein that moves water across bacterial membranes to maintain intracellular osmotic pressure33. The finding that GS2 C. concisus strains have aquaporin Z suggests that they may have enhanced abilities in adapting to environments where osmolarity frequently changes.…”
Section: Discussionmentioning
confidence: 99%
“…Aquaporin Z was found in all GS2 C. concisus strains, but not in any GS1 strains. Aquaporin Z is a protein that moves water across bacterial membranes to maintain intracellular osmotic pressure33. The finding that GS2 C. concisus strains have aquaporin Z suggests that they may have enhanced abilities in adapting to environments where osmolarity frequently changes.…”
Section: Discussionmentioning
confidence: 99%
“…These immune responses are referred to as 'epitope spreading'. Ren et al recently reported on the structural homology and cross-immunoreactivity between bacterial aquaporin Z and human AQP4 (15). Their findings indicate that infection affects the induction of the autoimmune response against AQP4 in NMO.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed this autoantibody as an important contributor to TM pathology. Viral or bacterial infections [3,4] may be prodromal factors of TM, commonly stimulating an inappropriate immune attack in spinal cord. On the other hand, many infections can induce direct neuronal invasion, resulting in spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%